Analysis of NTRK expression in gastric and esophageal adenocarcinoma (AGE) with pan-TRK immunohistochemistry - Arnold, Andrea; Daum, S.; Winterfeld, Moritz von; Berg, E.; Hummel, M.; Horst, D.; Rau, B.; Stein, U.; Treese, C. (Pathology, research and practice, 2019)
Small molecule inhibitors such as Larotrectinib have been recently approved in the treatment of patients with fusions of the neurotrophic-tropomyosin receptor tyrosine kinase (NTRK) genes 1-3. These genomic rearrangements have been reported across different tumor subtypes with a high prevalence in rare tumors. However, in gastric and esophageal adenocarcinoma (AGE) NTRK fusions have also been described in a subset of Asian patients. In order to study the prevalence of this alteration in Caucasian patients with AGE we performed immunohistochemistry for pan-NTRK in 438 formalin-fixed paraffin embedded (FFPE) tumor samples. While we found NTRK expression in gastric glands and tumor adjacent nerve tissue, we did not detect this marker in the tumor compartment. Based on our findings NTRK fusions do not seem to play a role in the molecularpathology of Caucasian AEG patients, so that other treatment options are required.
Gesehen am 22.01.2020